Pengambilan Keputusan Kredit: Pengaruh Literasi Keuangan, Suku Bunga, dan Inklusi Keuangan - Denny Hambali; Rizqi, Reza Muhammad (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to analyze the effect of financial literacy, interest rates, and financial inclusion on credit decision making at PT Busan Auto Finance in Sumbawa. In the face of increasing credit needs in the motor vehicle financing sector, it is important to understand the factors that influence consumer decisions. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS), involving 100 respondents who have taken credit in the past year. The results showed that financial literacy has a positive and significant effect on credit decision making. This means that the higher consumers' understanding of financial aspects, the wiser they are in making credit decisions. In contrast, interest rates have a negative and significant effect, which means that the higher the interest rate, the lower the public's interest in taking credit due to the high financial burden. Meanwhile, financial inclusion shows a positive and significant effect, indicating that wider access to formal financial services encourages increased credit taking. The R-square value of 0.728 indicates that the three variables are able to explain 72.8% of the variability in credit decision making. In addition, the Goodness of Fit (GoF) test yielded a value of 0.6247, indicating that the model has a good fit. The implications of the results emphasize the importance of improving financial literacy, managing competitive interest rates, and expanding access to formal financial services. The findings are expected to assist PT Busan Auto Finance in formulating more effective credit strategies and supporting the economic growth of the Sumbawa community.